Analisis Efektivitas Pelayanan Pendaftaran Rawat Jalan Melalui Aplikasi Sistem Berobat Jalan Online di Rumah Sakit Umum Daerah dr. Chasbullah AbdulMadjid Kota Bekasi - Irfan Choirul Fazri; Wahidin Septa Zahran (Jurnal Ilmu Administrasi Publik, 2023)
In handling a large number of queues and the gathering or overflowing of prospective patients at the registration counter, a breakthrough  in  health  services  is  needed  with  the  speed  and response of officers to prepare patient files or data appropriately. A long waiting time resulted in a lack of treatment support facilities and delays in information, so a health service was created by using an application called the Online Outpatient Treatment System (SIBEROJOL) application. This study aimed to provide outpatient health   services   online.   The   Regional   General   Hospital   dr. Chasbullah Abdulmadjid, Bekasi City has a web-based application called SIBEROJOL as a digital-based system that is used for services in storing data on prospective outpatient patients. The SIBEROJOL application has health services in online outpatient registration. The research   method   used   in   this   research   was   qualitative   with descriptive   research   type.   In   collecting   the   data,   researchers employed observation, documentation, and interviews. The researchers examined the object of study and hold direct interactions with informants. The results showed the effectiveness of outpatient registration services by applying the Online Outpatient Treatment System at the Regional General Hospital (RSUD)  dr. Chasbullah Abdulmadjid, Bekasi City, has not been effective because there were several obstacles. However, several efforts and solutions must be considered.